Carotid Lumen Diameter Is Associated With All‐Cause Mortality in the General Population. Issue 16 (18th August 2020) - Fritze, Felix; Groß, Stefan; Ittermann, Till; Völzke, Henry; Felix, Stephan B.; Schminke, Ulf; Dörr, Marcus; Bahls, Martin
Abstract : Background: Common carotid intima–media thickness (cIMT) is a biomarker for subclinical atherosclerosis and is associated with all‐cause as well as cardiovascular mortality. Higher cIMT is accompanied by a compensatory increase in lumen diameter (LD) of the common carotid arteries. Whether cIMT or LD carry more information with regard to mortality is unclear. Methods and Results: A total of 2751 subjects (median age 53 years; 52% female) were included. During a median follow‐up of 14.9 years (range: 12.8–16.5) a total of 506 subjects died. At baseline, cIMT and LD were assessed by carotid ultrasound scans. Multivariable Cox regression models were used to relate cIMT, LD, LD adjusted for cIMT (LD+cIMT), and LD/cIMT ratio with all‐cause, cardiovascular, and noncardiovascular mortality. All models were ranked using Akaike's information criterion. Harrel's c statistic was used to compare the models' predictive power for mortality. A 1‐mm increase in LD was related to a higher risk for all‐cause mortality (hazard ratio [HR], 1.29; 95% CI, 1.14–1.45, P <0.01). This association remained significant when cIMT was added to the model (HR, 1.26; 95% CI, 1.11–1.42; P <0.01). A 1‐mm higher cIMT was also related with greater mortality risk (HR, 1.73; 95% CI, 1.09–2.75). The LD/cIMT ratio was not associated with all‐cause mortality. LD had the lowest Akaike's information criterion regarding all‐cause mortality and improved all‐cause mortality prediction compared with the null model ( P =0.01). CIMT weakened all‐cause mortality prediction compared with the LD model. Conclusions: LD provided more information for all‐cause mortality compared with cIMT in a large population‐based sample.